PUBLIC TRUST IN NGOS IN KAZAKHSTAN - Amanbieke, Ailiya; Sagyndyk, Gulzhazira; Tleubekov, Talgatbek (Nazarbayev University Graduate School of Public Policy, 2025)
Public trust in various non-governmental organizations in Kazakhstan remains low. The representatives of NGO in Kazakhstan believe that the reduced level of public trust in civil society and specifically in non-governmental organizations is the main obstacle to its development. The main goal of this study is to define and analyze the key factors that influence the public trust in NGOs in Kazakhstan. To do so, we used the concurrent embedded mixed-methods approach and collected both qualitative and quantitative data . During this study we conducted a survey in the Kyzylorda Region and took semi-structured interviews with NGO representatives from different sectors and several regions of Kazakhstan. The findings of the study demonstrate that the level of public trust in NGOs in Kazakhstan is rather low. Notably, regression analysis shows that trust in government, political interest, media perception of NGOs, and frequency of interaction with NGOs are crucial factors that impact public trust, while demographic characteristics demonstrate a low influence.
Keywords: public trust; civil society; non-governmental organizations; Kyzylorda region; Type of access: Embargo